Unilateral intrastriatal 6-hydroxydopamine lesion in mice: a closer look into non-motor phenotype and glial response - Pinheiro, Bárbara Filipa Mendes (2021)
Parkinson’s disease (PD) is a prevalent movement disorder characterized by the progressive loss of dopaminergic neurons in substantia nigra pars compacta (SNpc). The 6-hydroxydopamine (6-OHDA) lesion is still one of the most widely used techniques for modeling Parkinson’s disease (PD) in rodents. Despite commonly used in rats, it can be challenging to reproduce a similar lesion in mice. Moreover, there is a lack of characterization of the extent of behavioral deficits and of the neuronal loss/neurotransmitter system in unilateral lesion mouse models. In this study, we present an extensive behavioral and histological characterization of a unilateral intrastriatal 6-OHDA mouse model. Our results indicate significant alterations in balance and fine motor coordination, voluntary locomotion, and in the asymmetry’s degree of forelimb use in 6-OHDA lesioned animals, accompanied by a decrease in self-care and motivational behavior, common features of depressive-like symptomatology. These results were accompanied by a decrease in tyrosine hydroxylase (TH)-labelling and dopamine levels within the nigrostriatal pathway. Additionally, we also identify a marked astrocytic reaction, as well as proliferative and reactive microglia in lesioned areas. These results confirm the use of unilateral intrastriatal 6-OHDA mice for the generation of a mild model of nigrostriatal degeneration and further evidences the recapitulation of key aspects of PD, thereby being suitable for future studies beholding new therapeutical interventions for this disease.